Processing and characterization of di- zinc stannate (Zn2SnO4) as potential anode for li-ion batteries - Chung, Darell Kingsley Wang Ting. (2012)
The demand for lithium ion batteries with higher capacities has seen the rise of tin based anodes from the conventional graphite anodes. By exploring the use of tin based anodes, we are able to reach a higher capacity for the batteries along with other benefits such as increased charging efficiency.